PENGARUH VARIASI KANDUNGAN AIR DI ATAS DAN DI BAWAH OPTIMUM MOISTURE CONTENT (OMC) TERHADAP NILAI CBR TANAH LEMPUNG - Yesaya A. S. Tuuk; Jeffrey A. Delarue; Rocky F. Roring (Sustainable Construction (SUSCON), 2024)
This research analyzes the characteristics of clay soil in the campus environment of State University of Manado through laboratory testing. Two soil samples were evaluated with variations of moisture content, 3% below and 3% above the Optimum Moisture Content (OMC) for laboratory CBR testing. Based on the standard proctor test results, the OMC values were approximately 23.25% for the first soil sample and 23% for the second soil sample, with a dry unit weight of around 1.44 g/cm³ for the first soil sample and 1.45 g/cm³ for the second soil sample. In the soaked CBR test, the soaked CBR values at the OMC variations were 5.81% for the first sample and 4.15% for the second sample. A 3% increase in moisture content above the OMC showed a decrease in CBR value by 5.72%, while a 3% decrease below the OMC resulted in a 5.97% increase in CBR value. This study provides a deep understanding of clay soil response to changes in moisture content, relevant for infrastructure planning and construction.